Planning for self-employment at the beginning of a market economy: Evidence from individual data of East German workers - Michael Lechner; Friedhelm Pfeiffer (Deutsches Institut für Wirtschaftsforschung (DIW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1992)
We investigate the plans of individual workers concerning future self-employment in the former German Democratic Republic (East Germany) shortly before the economic, monetary and social union in June/July 1990. In order to model these plans, we take detailed account of individual heterogeneity, the economic and social environment of the individual, and the situation of the firm in which the person is employed. Our data base is the Socio-Economic Panel (SOEP) East. We find that the desire to become an entrepreneur is basically determined by individual and household characteristics, including income and asset indicators, and not as much by the current job situation of the individual. The work experience attained in the socialist economy seems to be irrelevant for the decision to become self-employed in a market economy. Furthermore, we find evidence of barriers to entry which may come from capital market constraints and institutional restrictions. Due to the ordinal nature of the answers, we used the ordinal logit model for estimation. The corresponding stochastic assumptions are tested extensively using pseudo-Lagrange multiplier tests against omitted variables, non-linearity, asymmetry of distribution, and heteroscedasticity. We also present an estimation of the determinants of the probability of being self-employed in Summer 1990, where we find, due to institutional restrictions in the former GDR, only a few individual characteristics to be important.
Keywords: 330